Improvement of the System of Formation of Personnel Reserve of Municipal Service the Major Cities of Russia (through example of Rostov-on-Don) ("Journal "U". Economy. Management. Finance.", 2017)
In modern conditions the problem of formation of municipal bodies, are an important element of management policy. Approaches to staff selection and formation of a reserve are constantly changing, which determines the necessity of searching for effective forms of personnel reserve. The municipal authority is the Foundation of a stable system state that determines the relevance of effective personnel policy in this direction.
Keywords: municipal management; talent pool; competency-based approach; personnel policy